Correction: Truncated hexagonal bi-pyramidal gallium ferrite nanocrystals: integration of structural details with visible-light photo-activity and self-cleaning properties. Issue 27 (28th June 2018) - Mishra, Monali; Mukherjee, Indrani; Mall, Ashish Kumar; Mitra, Arijit; Dash, Sukalyan; Chatterjee, Sriparna; Mukherjee, Somdutta; Roy, Amritendu
Abstract : Correction for 'Truncated hexagonal bi-pyramidal gallium ferrite nanocrystals: integration of structural details with visible-light photo-activity and self-cleaning properties' by Monali Mishra et al., J. Mater. Chem. A, 2018, DOI: ;10.1039/c8ta02749h .